2020
DOI: 10.3390/w12123484
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three Different Native Plant Mixtures for Extensive Green Roofs in a Humid Subtropical Climate Context

Abstract: Most of the services and benefits of green roofs are related to the substrate as well as the vegetation layer. Although plant selection should be made on the basis of green roof typology, morphology, and climate conditions, very often, Sedum species only are used worldwide. However, they do not always guarantee the best performances; hence, it is important to investigate different plant species and their performance in different climate contexts. Herein, an experiment was conducted using three plant mixes (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…An average Ks value of 0.85 was reported by Voyde [56] for the well-watered sedum measured using 0.072 m 2 weighing trays in Auckland, New Zealand; whereas, Schneider [57] observed Ks values range 1.0 to 1.7 for sedums measured with a 0.21 m 2 weighing lysimeter in Villanova, PA. An average Ks value of 1.35 was observed by Rezaei [46] for sedums from 0.56 m 2 indoor greenhouse trays. Zanin and Bortolini [58] also found Ks value of sedum as 0.57 for extensive green roofs in a humid subtropical climate. Starry et al [59] reported the Ks values for three sedum species, ranging from 0.21 to 0.50 for sedum album, from 0.22 to 0.55 for sedum sexangulare and from 0.25 to 0.71 for sedum kamtschaticum, respectively.…”
Section: Estimation Of Crop Coefficientmentioning
confidence: 89%
“…An average Ks value of 0.85 was reported by Voyde [56] for the well-watered sedum measured using 0.072 m 2 weighing trays in Auckland, New Zealand; whereas, Schneider [57] observed Ks values range 1.0 to 1.7 for sedums measured with a 0.21 m 2 weighing lysimeter in Villanova, PA. An average Ks value of 1.35 was observed by Rezaei [46] for sedums from 0.56 m 2 indoor greenhouse trays. Zanin and Bortolini [58] also found Ks value of sedum as 0.57 for extensive green roofs in a humid subtropical climate. Starry et al [59] reported the Ks values for three sedum species, ranging from 0.21 to 0.50 for sedum album, from 0.22 to 0.55 for sedum sexangulare and from 0.25 to 0.71 for sedum kamtschaticum, respectively.…”
Section: Estimation Of Crop Coefficientmentioning
confidence: 89%
“…As for plant mix effect, the results show that the Sedum mixture was found to be significantly less effective in retaining rainwater, while the use of herbaceous perennial and suffruticose plants, instead, was an excellent solution to reduce outflows. However, it has to be stated that the latter two treatments have shown the lowest resistance to summer water stress and progressively succumbed, when in the summer of 2016 irrigation was stopped [62]. Vice versa, Sedum plants were minimally affected by the summer drought, showing that they are able to ensure almost complete survival after two years from planting [75].…”
Section: Discussionmentioning
confidence: 99%
“…Monthly actual evapotranspiration and crop coefficient (Kc act) were calculated according to [60,61]. These results and their discussion are reported in [62].…”
Section: Methodsmentioning
confidence: 99%
“…while providing ecosystem services and additional benefits for the city. Many studies have investigated the influence of individual SCMs on the quantity and quality of stormwater in urban sub-catchments, i.e., on a micro-scale [5][6][7][8]. Moreover, models are being used to design SCMs and predict SCM performance for different design and weather scenarios [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Three types of infiltration trenches 4. Three types of rain gardens 5. Three types of bio-retention cells 6.…”
mentioning
confidence: 99%